Frontispiece: Intermetallic Nanocrystals: Seed‐Mediated Synthesis and Applications in Electrocatalytic Reduction Reactions. Issue 69 (9th December 2022) - Guo, Jingchun; Jiao, Shilong; Ya, Xiuying; Zheng, Huiling; Wang, Ran; Yu, Jiao; Wang, Huanyu; Zhang, Zhilin; Liu, Wei; He, Congxiao; Fu, Xucheng
Abstract : Throwing the seed : This review comprehensively summarizes the preparation of intermetallic nanocrystals (IMNCs) by three approaches of seed‐mediated synthesis: seed‐mediated growth, seed‐mediated transformation, and seed‐mediated co‐reduction. The precise control over the size, shape, composition, structure and exposed crystal facet of IMNCs by seed‐mediated synthesis and their widespread applications in electrocatalytic reduction reactions are summarized. After that, the current challenges associated with the controllable synthesis of IMNCs and conclude the article with perspectives are addressed (DOI: 10.1002/chem.202202221 ).